Chinese law in context - Liu, Chenglin (Carolina Academic Press, 2020)
"This book serves as an overview of contemporary Chinese law and the history of Chinese Law. More than a simple casebook, this book will be useful to students and researchers alike as an introduction to Chinese Law"--
1911
Keywords: Law / China; Law / China / History; Law / China / Philosophy; Confucianism and law; Law; Law / Philosophy; China; History